Clot Migration Is Associated With Intravenous Thrombolysis in the Setting of Acute Ischemic Stroke. Issue 12 (December 2018) - Ren, Yifan; Churilov, Leonid; Mitchell, Peter; Dowling, Richard; Bush, Steve; Yan, Bernard
Abstract : Background and Purpose—: Clot migration to distal intracranial arterial segments was observed in patients presented with acute large vessel occlusions. It is postulated that the exposure of patients to intravenous thrombolysis (IVT) increases the risk of clot migration and associated with inaccessibility of the clot by endovascular thrombectomy (EVT). In this study, we aimed to investigate the incidence of clot migration and its association with IVT before EVT. Methods—: We conducted a single-center retrospective analysis of patients who had EVT during the period 2009 to 2016. Patients who fulfilled clinical criteria were treated with bridging IVT and those who did not were treated with direct EVT. Clot position was assessed by pretreatment computed tomography angiogram or magnetic resonance angiogram and was compared with clot position identified by digital subtraction angiography before planned endovascular thrombectomy. Results—: Of 314 included patients, clot migration occurred in 43 patients (13.7%). The proportion of clot migration was 18.7% (39 of 209) in patients who had bridging IVT with EVT compared with 3.8% (4 of 105) in direct EVT ( P =0.001). Of the 39 patients who had clot migration in the bridging IVT with EVT, 59.0% (23 of 39) demonstrated clot inaccessibility compared with 25.0% (1 of 4) in clot migration cases in the direct EVT group ( P =0.011). Conclusions—: The incidence of clot migration was significantly increased in the setting of bridging IVT before EVT, leading to increased proportion of clot inaccessibility by EVT. Abstract : Supplemental Digital Content is available in the text.